Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3390/s150714830
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Remotely Sensing Vital Signs of Human Subjects Outdoors

Abstract: After chemical or nuclear leakage or explosions, finding survivors is a huge challenge. Although human bodies can be found by smart vehicles and drones equipped with cameras, it is difficult to verify if the person is alive or dead this way. This paper describes a continuous wave radar sensor for remotely sensing the vital signs of human subjects. Firstly, a compact and portable 24 GHz Doppler radar system is designed to conduct non-contact detection of respiration signal. Secondly, in order to improve the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…Facing the problems of interference from the environment, Wang et al proposed a combined method in [27], consisting of several general methods to extract periodic signals from noise and clutter, and they also concluded that the performance improvement is not satisfied by using only one method.…”
Section: Detection Algorithmmentioning
confidence: 99%
“…Facing the problems of interference from the environment, Wang et al proposed a combined method in [27], consisting of several general methods to extract periodic signals from noise and clutter, and they also concluded that the performance improvement is not satisfied by using only one method.…”
Section: Detection Algorithmmentioning
confidence: 99%
“…As the signal processing proposed in [31], facing the same problems of moving interference of the environment, the combined methods was proposed, which includes several ordinary methods of extracting periodic signal from noise, such as self-correlation, adaptive line enhancer (ALE), blind source separation (BBS), EMD, etc., and concludes the effect is not obvious when only using one of the methods mentioned. For sensing the human subject outdoors in [31], it is necessary to remove interference continuously, so ALE is added to reduce the Gaussian noise signal of the detected respiration adaptively.…”
Section: Detection Algorithmmentioning
confidence: 99%
“…For sensing the human subject outdoors in [31], it is necessary to remove interference continuously, so ALE is added to reduce the Gaussian noise signal of the detected respiration adaptively. But for the remotely sensing vital signs including not only the respiration but heartbeat, the higher SNR improvement is required.…”
Section: Detection Algorithmmentioning
confidence: 99%
“…Facing the problems of moving interference from the environment, the combined methods are proposed in [27], which include several ordinary methods of extracting periodic signal from noise such as using an adaptive line enhancer (ALE), blind source separation, empirical mode decomposition (EMD), etc., and [27] concludes that the effect is not obvious when using one method of the mentioned methods. In sensing a human subject outdoors in [27], it is necessary to remove interference continuously, so ALE is added to reduce the Gaussian noise signal of the detected respiration adaptively.…”
Section: Detection Algorithmmentioning
confidence: 99%
“…In sensing a human subject outdoors in [27], it is necessary to remove interference continuously, so ALE is added to reduce the Gaussian noise signal of the detected respiration adaptively. However, for the remotely sensing of vital signs including not only respiration but also heartbeat, higher SNR improvement is required.…”
Section: Detection Algorithmmentioning
confidence: 99%